Harmonization of company taxation systems - Heinrich Hölzler (Intereconomics, 1976)
The author of the following article gives a survey of the different corporation tax systems and rates in the individual EC-member countries, explains the need for a harmonization of direct company taxation within the Community, and discusses the Commission's recent proposal as compared with other possible approaches.
Keywords: 330; EC